Concentrating stroke care provision in the Czech Republic: The establishment of Stroke Centres in 2011 has led to improved outcomes - Bryndová, Lucie; Bar, Michal; Herzig, Roman; Mikulík, Robert; Neumann, Jiří; Šaňák, Daniel; Škoda, Ondřej; Školoudík, David; Václavík, Daniel; Tomek, Aleš (Health policy (Amsterdam, Netherlands), 2021)
This article describes policy processes that have led to the re-organisation of stroke care in the Czech Republic since 2011, which has been part of a broader process of care concentration in several medical fields. Currently, stroke care is provided by 13 Comprehensive and 32 Primary Stroke Centres. The paper explains factors that supported the reform implementation, reviews implications, and discusses future challenges. Mandatory reporting of quality indicators, the introduction of a benchmarking system, integration with pre-hospital emergency care, and the introduction of countrywide patient triage have supported more timely treatment for stroke patients and better quality of care. Data from the Stroke Care Quality Indicators of the Czech Stroke Society show positive trends in many areas: the number of patients treated with intravenous thrombolysis quadrupled in eight years, with 26.4 % of all acute stroke patients receiving thrombolysis in 2018. Czech Republic now ranks third in Europe in the number of thrombolysis per population and second in the number of mechanical thrombectomies per population. The Czech experience provides an example of positive outcomes of concentrated stroke care, while highlighting the importance of proper implementation processes. In particular, it is essential to involve stakeholders and to provide reputational incentives through continuous benchmarking.
Keywords: Highly specialized care concentration; benchmarking; cévní mozková příhoda; Czech Republic; lidé; kvalita zdravotní péče; Quality monitoring; Recanalization therapy; Evropa; Humans; Stroke; Česká republika; Quality of Health Care; Europe; Benchmarking